FENOLOGI SEMANGKA (CITRULLUS LANATUS (THUNB.)) PADA KONDISI LINGKUNGAN YANG BERBEDA - Karisa Ivana; Vauzia; Irma Leilani Eka Putri (Jurnal Biogenerasi, 2026)
Watermelon (Citrullus lanatus (Thunb.)) is a horticultural crop with high economic value with a water content of up to 92% and is rich in vitamins A, E, and antioxidants. Watermelon is highly dependent on environmental conditions to grow well. Good environmental conditions certainly affect watermelon productivity. In order to develop watermelon cultivation efforts, it is necessary to conduct biological studies of watermelon, one of which is regarding the phenology of watermelon (Citrullus lanatus (Thunb.)) under different environmental conditions. This study was conducted from November 2025 to February 2026 in two locations, namely Bayang District, Pesisir Selatan Regency and Sangir District, Solok Selatan Regency with observation samples at each location of 20 replications. The parameters observed included flower emergence time, flowering duration, fruit emergence time, and fruiting duration at each location. Data were analyzed using a t-test with a significance level of 5%. The results of the study showed that there were differences in watermelon phenology from all aspects of observation, namely flower emergence time, flowering duration, fruit emergence time, and fruiting duration in the two research locations, where in Bayang District the average flower emergence time was 28.7 days after planting (DAP), flowering duration was 16.35 days, fruit emergence time was 45.05 DAP, fruiting duration was 39.5 days. In Sangir District the average flower emergence time was 19.2 DAP, flowering duration was 19.2 days, fruit emergence time was 35.3 days, and fruiting duration was 32.65 days.